1975
DOI: 10.1159/000221838
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Isonicotinic Acid Hydrazide in Serum

Abstract: A method for the determination of isonicotinic acid hydrazide is given. The hydrazide is complexed with cupric ions and condensated with an aromatic aldehyde substituted in ortho-position with a hydroxyl group. The method is adapted to the AutoAnalyzer equipment of first and second generation. Pilot measurements on the pharmacokinetic behaviour of isonicotinic acid hydrazide are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Almost all of the functions of CD147 that have been investigated to date have been associated with the membrane portion of CD147 [ 35 ]. We have previously reported that CD147 distributes to the cytoplasm in certain metastatic melanomas and have identified novel functions of CD147 in the endoplasmic reticulum (ER), including maintaining both calcium homeostasis and mitochondrial function [ 21 , 36 ]. This study identified the nuclear envelope distribution of CD147 in melanoma and highlights a novel mechanism of CD14 7 in controlling melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the functions of CD147 that have been investigated to date have been associated with the membrane portion of CD147 [ 35 ]. We have previously reported that CD147 distributes to the cytoplasm in certain metastatic melanomas and have identified novel functions of CD147 in the endoplasmic reticulum (ER), including maintaining both calcium homeostasis and mitochondrial function [ 21 , 36 ]. This study identified the nuclear envelope distribution of CD147 in melanoma and highlights a novel mechanism of CD14 7 in controlling melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%